2005
DOI: 10.1103/physrevlett.94.147601
|View full text |Cite
|
Sign up to set email alerts
|

Order-Disorder Component in the Phase Transition Mechanism ofO18Enriched Strontium Titanate

Abstract: Ti and Sr nuclear magnetic resonance spectra of 18O enriched SrTiO3 (STO-18) provide direct evidence for Ti disorder already in the cubic phase and show that the ferroelectric transition at T(C)=24 K occurs in two steps. Below 70 K rhombohedral polar clusters are formed in the tetragonal matrix. These clusters subsequently grow in concentration, freeze out, and percolate, leading to an inhomogeneous ferroelectric state below T(C). This shows that the elusive ferroelectric transition in STO-18 is indeed connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
39
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 21 publications
11
39
0
2
Order By: Relevance
“…Dead layers have been discussed in the context of ferroelectrics, where they are often proposed as explanations for the worsening of the dielectric constant of thin films, although the exact nature, thickness, and even location of the dead layer, which might be inside the electrode, is still a subject of debate (Sinnamon, Bowman, and Gregg, 2001;Stengel and Spaldin, 2006;Chang et al, 2009). In ferroelectrics, dead layers prevent screening causing domains to appear (Bjorkstam and Oettel, 1967;Kopal et al, 1999;Bratkovsky and Levanyuk, 2000). More recently, Luk'yanchuk et al (2009) proposed that an analogous phenomenon may take place in ferroelastics, so that ''ferroelastic dead layers'' can cause the formation of twins (Fig.…”
Section: Domains a Boundary Conditions And The Formation Of Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dead layers have been discussed in the context of ferroelectrics, where they are often proposed as explanations for the worsening of the dielectric constant of thin films, although the exact nature, thickness, and even location of the dead layer, which might be inside the electrode, is still a subject of debate (Sinnamon, Bowman, and Gregg, 2001;Stengel and Spaldin, 2006;Chang et al, 2009). In ferroelectrics, dead layers prevent screening causing domains to appear (Bjorkstam and Oettel, 1967;Kopal et al, 1999;Bratkovsky and Levanyuk, 2000). More recently, Luk'yanchuk et al (2009) proposed that an analogous phenomenon may take place in ferroelastics, so that ''ferroelastic dead layers'' can cause the formation of twins (Fig.…”
Section: Domains a Boundary Conditions And The Formation Of Domainsmentioning
confidence: 99%
“…However, polar nanodomains have been detected even in the normal 16 O composition of SrTiO 3 (Uesu et al, 2004;Blinc et al, 2005), and their local symmetry is triclinic and not tetragonal (Blinc et al, 2005). The ferroelectric phase of the heavyisotope composition is also poorly understood, but it has finely structured nanodomains reminiscent of those observed in relaxors (Uesu et al, 2004;Shigenari et al, 2006), while relaxorlike behavior has also been observed in SrTiO 3 thin films (Jang et al, 2010).…”
Section: G Nanodomains In Bulkmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 STO is also a perfect prototype to investigate phase transition, 3 especially to understand the surface and interface structural configuration for the perovskite films grown on it. 4 Although ferroelectric properties were only reported through oxygen isotope exchange ͑ST 18 O͒, 3,5 and cation substitution, 6,7 recent theories and experiments validate the existence of ferroeletricity in STO thin films under strain. [8][9][10] He et al [11][12][13] systematically studied the structural phase transition of STO thin films under strain.…”
mentioning
confidence: 99%
“…SrTiO 3 ͑STO͒ is an incipient ferroelectric material in perovskite structure, which has been extensively studied for its application in tunable microwave devices for having a large and variable dielectric constant. 1,2 STO is also a perfect prototype to investigate phase transition, 3 especially to understand the surface and interface structural configuration for the perovskite films grown on it.…”
mentioning
confidence: 99%